Long-term outcomes of ophthalmosurgery in diabetic patients - Dmitriy Valentinovich Lipatov; Elena Grigor'evna Bessmertnaya; Anatoliy Gennad'evich Kuzmin; Nataliya Borisovna Smirnova; Anna Anatol'evna Tolkacheva; Timofey Alexandrovich Chistyakov (Сахарный диабет)
Diabetes morbidity grows steadily despite recent progress in its diagnostics and treatment. Its most frequent complication is retinopathy although thereare increasingly more cases of diabetic cataract, secondary rubeous (neovascular) glaucoma, eyelid diseases, and transient impairment of vision.Aim To analyse late results of ophthalmosurgery in diabetic patients with vision problems.Materials and methods Over 24,000 patients were examined from January 2006 to November 2010 at the Department of Diabetic Retinopathyand Ophthalmosurgery, Endocrinological Research Centre. Results of more than 2660 seances of retinal laser coagulation and about 350 surgicalinterventions for diabetic cataract and secondary neovascular glaucoma were available for analysis.Conclusion Timely and correct application of retinal laser coagulation, modern facoemulsification of complicated cataract and drainage surgeryof uncompensated secondary rubeous glaucoma produces good functional results and permits to preserve or even improve visual acuity. The efficacyof surgical intervention is directly related to the quality of diabetes compensation and depends on the joint efforts of ophthalmologists, endocrinologists,and anesthesiologists.